Analysis The Influence of Country of Origin and Brand Image on Purchase Intentions through Customer Uncertainty (Study Case on OPPO Smartphone) - Javier Berliando; Amie Kusuma Wardhani (JURNAL STUDI MANAJEMEN ORGANISASI, 2022)
Changes in trade activities have occurred as a result of changing times, and technical improvements have benefited corporations or business players in extending or growing markets that are no longer restricted to a single nation but may penetrate other countries. The emergence of foreign products, such as mobile phones, widen the choices of mobile phones in the Indonesian market. The majority of mobile phone brands purchased by Indonesian consumers are from China, despite the fact that the majority of the world regards China as having product stereotypes or product images that are of poor quality, cheap, and frequently counterfeited, resulting in a discontinuity with the product image they have. This study examines and analyses the effect of country of origin and brand image on purchase intentions through customer uncertainty on OPPO smartphone. The study sample included customer over 18 years old who has purchased and used OPPO smartphone. The sample in this study was 200 respondents. The method used in this study is a structural equation model (SEM) with the help of AMOS software for hypotheses test. The results of this study show country of origin and brand image has a negative effect on customer uncertainty, country of origin and brand image has a positive effect on purchase intention, whereas customer uncertainty has a negative effect on purchase intention. This study significantly extends managerial implications for OPPO to focus heavily to solve customer uncertainty by advertising product performance and giving detailed information about the product (such as label) to lower customer uncertainty and encourage customer to have intention to purchase OPPO smartphone. secondly, to solve customer uncertainty OPPO need to eliminate China’s (OPPO country of origin) stereotype as a country with a poor product.